BIBLICAL PERSONAGES AND J. FOWLES NOVEL CHARACTERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Currently intertextuality is one of the most discussable issues concerning modern and postmodern literature, as modern and postmodern writers are characterized by the implementation of intertextual components in their writings. J.Fowles, a postmodern British writer stands among those writers. Despite the fact that there have been numerous investigations on the issue of intertextuality in his works, none of them has been devoted to the study of the philosophical essay ‘’The Aristos’’ as a background source for his other writings. The aim of the present article is to define the nature of novel characters departing from his interpretation of biblical personages: Adam and Eve, stated in his philosophical essay ‘’The Aristos’’. The study becomes especially important as the male and female characters in all his novels allude to this interpretation.  The intertextual ties between the author’s works are as important as intertextual connections between different authors’ works. In fact, ‘’The Aristos’’ is one of the author’s lesser studied works. Nevertheless to understand J.Fowles’ novels properly one should refer to ‘’The Aristos’’. All his female characters impersonify Eve and male characters - Adam - in line with his own interpretation of Adam’s temptation.  The analysis has shown that J. Fowles considers women as wise, kind, tolerant and progressive. In contrast, men are considered to be static, inactive and not capable of changes. Moreover, women are responsible for changes and progress both in the life of the society and in the life of men. The author also believes that there have been Eve societies, such as Renaissance and the present era, in which the woman, the mother, female gods encourage innovation and experiment, fresh definitions, aims, modes of feeling;  and Adam societies, such as  Victorian, in which the man, the father, male gods demand strict obedience to established institutions and norms of bahaviour.